On the flexural stiffness of 3D printer thermoplastic. Issue 1 (January 2017) - Virgin, Lawrence
This paper describes the process of estimating Young's modulus for the thermoplastic material commonly used in a type of 3D printer. Its twin goals are to compare and contrast a number of simple techniques from elementary structural analysis and to assess the influence of the printer density settings and print orientation (effective material anisotropy). Since components printed using additive manufacturing are used extensively for student projects, often involving load-bearing components, this contribution seeks to shed some light on fundamental modeling issues